2008
DOI: 10.1007/s10943-008-9197-7
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Under-Five Mortality in Nigeria: Differentials by Religious Affiliation of the Mother

Abstract: Observations in Nigeria have indicated polio vaccination refusal related to religion that ultimately affected child morbidity and mortality. This study assessed the role of religion in under-five (0-59 months) mortality using a cross-sectional, nationally representative sample of 7,620 women aged 15-49 years from the 2003 Nigeria Demographic and Health Survey and included 6,029 children. Results show that mother's affiliation to Traditional indigenous religion is significantly associated with increased under-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…In Cameroon, childhood feeding practices varies between Muslims and non-Muslims in the northern region [97]. Under-5 mortality is influenced by religious affiliation and cultural beliefs in Cameroon and Nigeria [100, 101]. Child characteristics that were controlled included birth weight (<2.5 kg and >2.5 kg), multiple or single birth, birth order, child’s sex, and experience of diarrhoea two weeks before the survey.…”
Section: Methodsmentioning
confidence: 99%
“…In Cameroon, childhood feeding practices varies between Muslims and non-Muslims in the northern region [97]. Under-5 mortality is influenced by religious affiliation and cultural beliefs in Cameroon and Nigeria [100, 101]. Child characteristics that were controlled included birth weight (<2.5 kg and >2.5 kg), multiple or single birth, birth order, child’s sex, and experience of diarrhoea two weeks before the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Some residents felt they were being targeted by Western biomedicine as a result of their religion [43]. Increased underfive mortality in Nigeria is also significantly associated with maternal affiliation with a traditional indigenous religion, primarily owing to differential use of maternal and child health services [45]. In Pakistan, vaccine refusals are concentrated among low income individuals of Pashtun ethnicity.…”
Section: (B) Religious and Cultural Objectionsmentioning
confidence: 99%
“…Regional differences in African Geographical Review 3 socioeconomic conditions have been found to be powerful explanatory factors causing spatial differential in child mortality in Malawi (Kalipeni, 1993). Considerable efforts have been put into studying various factors affecting child mortality in Nigeria (Antai, 2011;Antai, Ghilagaber, Wedrén, Macassa, & Moradi, 2009;Caldwell, 1979;Folasade, 2000;Mesike & Mojekwu, 2012;Ogunjuyigbe, 2004;Orubuloye & Caldwell, 1975). Most of these studies have, however, neglected the spatial aspect that allows studying differences in the determinants at local level.…”
Section: Introductionmentioning
confidence: 99%